The European Union and Belarus: democracy promotion by technocratic means?. Issue 4 (6th June 2016) - Korosteleva, Elena A.
Abstract : Is Belarus an enviable constant in international relations: a maverick, isolated from the West and inseparable from the East? On the surface, there seems to be business as usual: Lukashenko's regime remains unchallenged; Belarus' relations with the European Union – spasmodic at best; while its absorption into Russia's Eurasian project continues apace. Yet, some critical disjunctures – manifested in government tacit resistance to Russia's influence, and more instructively, in people's growing affinity with Europe – may indicate a sea-change transformation in the very fabric of society. This article, utilizing extensive and subject-focused research, conducted in the country between 2009 and 2013, examines the nature and causalities of the occurring change. It argues that democracy promotion, in Belarus' case, may work better when depoliticized and inculcated, through norms, regulations, and practices of international order, into the daily lives of individuals. Through its continued technocratic, inclusive, and sector-level engagement, European Union governance, even under the conditions of limited bilateral dialogue, have succeeded in fostering much-needed space for reciprocal learning and critical reasoning, which may have far greater transformative potential than manufacturing a single collective will for democracy building.